Pequenas empresas e mercados globais: uma análise sobre a internacionalização de pequenas empresas do estado de Goías (Brasil) - Oliveira, Valéria da Consolação (Universidade do Vale do Rio dos Sinos, 2010)
The purpose of this work is to contribute to the study of international entrepreneurship in Brazil, through an explanatory analysis of the internationalization of small businesses of a state that is part of a region with late industrialization, The Center?West region of Brazil. The shortage of empirical studies revealing the characteristics of this phenomenon in the Center-West region of the country motivated this study. It started from the understanding that an analysis of the entrepreneurial activity related to internationalization in a region of late industrialization, could reveal new tendencies to be observed. In this context, the objective of the research described in this study, is to analyze the strategies adopted by small companies of the state of Goiás, Brazil, to the insertion in international markets. This analysis focused in the characteristics of the process of internationalization of the companies researched, in the characteristics of the ways they entered the international market; in the aspects of the marketing strategies that favor the international insertion; in the aspects of acquisition of knowledge associated to international activity; in the difficulties faced by the companies in internationalization and in the effects of the international activity over the performance of the companies in the national market. The theoretical referral considered to sustain the analyses, were theories that explain the general process of internationalization, in particular, studies about the internationalization of small companies. The study also relies in studies about internationalization strategies, international marketing, acquisition of knowledge and difficulties associated to internationalization and its performance in the national market after internationalization. The research of exploratory and descriptive nature was done in two phases. The first phase, through the consolidation of existing data, 94 small businesses in the state of Goiás that have activities associated to internationalization, were identified. The second phase, data was collected through a questionnaire applied to 41 of the 94 companies. The data analyses revealed that the small companies investigated in the state of Goiás, developed their process of internationalization taking advantage of opportunities that emerged from manager?s network relationships. The attractiveness of the products is not only associated to its cost but also to its customization. In the manager?s perception, international activity favors the improvement of the products or services offered by the company in the national market. The data also revealed that the knowledge of the international activity can be favored by actions at the level of public institutions and that the excess of regulations stands out as the barrier to the development of international activity. In conclusion, the study infer that international entrepreneurship can be considered as an alternative to the development of small businesses of the State of Goiás, making an impact in the country. The realization of other studies is suggested, for a wider analyze of the resources and necessary capabilities in different industrial sectors, to increment this activity.
Keywords: Pequenas empresas; Marketing internacional; Small firms; International entrepreneurship; International marketing; Empreendedorismo internacional; ACCNPQ::Ciências Sociais Aplicadas::Administração